2018
DOI: 10.1002/uog.19044
|View full text |Cite
|
Sign up to set email alerts
|

Traditionally vs sonographically coached pushing in second stage of labor: a pilot randomized controlled trial

Abstract: Our preliminary data suggest that transperineal ultrasound may be a useful adjunct to coached pushing during the active second stage of labor. Further studies are required to confirm these findings and better define the benefits of this approach. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…The sonographic coaching group observed the progress of the fetal head on the screen, while the other group did not. The sonographic coaching group had a significantly shorter second stage of labor 23 . Gilboa et al have shown that women who received visual biofeedback during labor had a more effective pushing technique and felt a stronger connection to the newborn after birth 24 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The sonographic coaching group observed the progress of the fetal head on the screen, while the other group did not. The sonographic coaching group had a significantly shorter second stage of labor 23 . Gilboa et al have shown that women who received visual biofeedback during labor had a more effective pushing technique and felt a stronger connection to the newborn after birth 24 .…”
Section: Discussionmentioning
confidence: 87%
“…The sonographic coaching group observed the progress of the fetal head on the screen, while the other group did not. The sonographic coaching group had a significantly shorter second stage of labor. Gilboa et al .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such interventions may include ultrasound coaching by visual feedback which has been reported to be beneficial when used in the labor ward. 41,42…”
Section: Research Implicationsmentioning
confidence: 99%
“…Given that informal literature reviews are frequently found to be selective and avoid contradictory studies, the gold standard for this process should be performing a formal systematic review prior to embarking on a new trial. Of three new trials of therapeutic interventions in obstetrics published in this journal last year, all made reference to prior work in their field but only one referred to a systematic review of the literature on the topic. Even in this study, the systematic review mentioned was published after the trial recruitment had ended, so clearly it was not used to inform the trial design.…”
Section: The Problem Of Research Waste In Obstetricsmentioning
confidence: 99%